Chapter 23 Fire, native ecological knowledge, and the enduring anthropogenic landscapes of Yosemite Valley - Deur, Douglas (Taylor & Francis, 2021)
Yosemite Valley is a place with rich and enduring traditions of Indigenous Ecological Knowledge, manifesting in specific management practices that, in turn, leave discernible imprints upon the natural landscape. Historically, the Native American inhabitants of Yosemite Valley have employed a variety of techniques that materially enhance the availability of culturally preferred plant communities. This chapter identifies specific techniques that appear consistently in the oral traditions and written historical accounts of the valley. These methods included anthropogenic burning, pruning and coppicing, clearing underbrush beneath trees, hand eradication ("weeding") of certain competing species, selective harvesting, smoking, "knocking" of dead wood from the tree, and other practices associated with both mundane activities and the spiritual beliefs of tribal communities traditionally associated with Yosemite. The displacement of Native peoples has dramatically and adversely impacted both Native communities and the landscape of the valley and plant communities with which they are connected.